MANAGEMENT OF CHANGES IN THE PROCESS OF STRUCTURAL ORGANIZATIONAL OPERATIONS ON THE EXPERIENCE OF TNCS - Гужуман, Лилия; Мешко, Наталья (SWorldJournal, 2020)
Given the constant development of the market and its acquisition of the characteristics of global capitalization, companies must monitor and apply all possible methods to maintain their position and improve growth and profitability. The current state of